L’espace vert public, lieu d’interactions entre société et biodiversité - Lotfi Mehdi; Francesca Di Pietro (Projets de Paysage)
It is estimated that by 2050, 75 % of the world population will live in urban areas. From now on biodiversity has become a major challenge for new strategies of urbanization. The aims of this paper are to study the impact of users’ practices on plant communities of public green spaces on the one hand, and help developing a model explaining the use of public green areas in relation to users’ practices and representations, on the other hand.